Exercise‐induced α‐ketoglutaric acid stimulates muscle hypertrophy and fat loss through OXGR1‐dependent adrenal activation. (27th February 2020) - Yuan, Yexian; Xu, Pingwen; Jiang, Qingyan; Cai, Xingcai; Wang, Tao; Peng, Wentong; Sun, Jiajie; Zhu, Canjun; Zhang, Cha; Yue, Dong; He, Zhihui; Yang, Jinping; et al.
Abstract: Beneficial effects of resistance exercise on metabolic health and particularly muscle hypertrophy and fat loss are well established, but the underlying chemical and physiological mechanisms are not fully understood. Here, we identified a myometabolite‐mediated metabolic pathway that is essential for the beneficial metabolic effects of resistance exercise in mice. We showed that substantial accumulation of the tricarboxylic acid cycle intermediate α‐ketoglutaric acid (AKG) is a metabolic signature of resistance exercise performance. Interestingly, human plasma AKG level is also negatively correlated with BMI. Pharmacological elevation of circulating AKG induces muscle hypertrophy, brown adipose tissue (BAT) thermogenesis, and white adipose tissue (WAT) lipolysis in vivo . We further found that AKG stimulates the adrenal release of adrenaline through 2‐oxoglutarate receptor 1 (OXGR1) expressed in adrenal glands. Finally, by using both loss‐of‐function and gain‐of‐function mouse models, we showed that OXGR1 is essential for AKG‐mediated exercise‐induced beneficial metabolic effects. These findings reveal an unappreciated mechanism for the salutary effects of resistance exercise, using AKG as a systemically derived molecule for adrenal stimulation of muscle hypertrophy and fat loss. Synopsis: The mechanisms underlying the beneficial effects of resistance exercise on body metabolism are poorly understood. Here, the Krebs cycle intermediate α‐ketoglutaric acid (AKG) is identified as an exercise‐induced, muscle‐derived metabolite, enhancing muscle growth and lipolysis via systemic stimulation of the adrenal gland. Acute resistance exercise increases plasma AKG levels and muscular AKG synthesis. AKG induces muscle hypertrophy and fat loss in vivo in mouse obesity models. AKG activates the adrenal gland, enhancing enhanced thermogenesis and lipolysis. OXGR1 is required for AKG‐mediated secretion of serum E. Abstract : The Krebs cycle intermediate α‐ketoglutaric acid acts as a systemic myometabolite promoting energy expenditure and lipolysis in mice.